Introduction to cost estimation related to natural damages and mitigation work costs through the use of simulation techniques - Masciarelli, Edgardo Alberto (2025)
The way to address natural hazards when carrying out project evaluations is through the valuation of the costs involved (mitigation works costs, damage repair costs, indirect costs to society, etc.). These costs are dependent on random variables and, as such, have associated probabilistic and risk characteristics. This concept can be further elaborated by stating that the way to address Natural Hazards in Project Evaluation is through the probabilistic valuation of the costs resulting from the occurrence of a natural disaster, the investments in mitigation works, and under the consideration of the associated risk. The methodology to be applied and related comments have already been addressed by the authors in previous works (Masciarelli et al.; 1997a, 1997b, 1997c, 1997d, 2000a, 2000b, 2000c, 2000d and Arranz et al.; 2000).